Cine ecuatoriano: Estrategia de producción implementadas en épocas de pandemia - Suárez Ayala, Jonathan Adonis (2022)
The present work seeks to describe the strategies implemented in the production of Ecuadorian cinema in times of pandemic, during the year 2020 and the first semester of 2021, a period affected by multiple factors, including the economic, political and health crisis that the country was experiencing. country, in addition to a low digital culture and a complex socioeconomic reality. This work is carried out under a qualitative exploratory research, which allows collecting information through primary sources. That is, through interviews with film producers, actors, directors and production graduates. In addition, the observation and collection of information is used through secondary sources such as journalistic notes from the main national media, the most used methodology in this work is the qualitative one. It is concluded that, from the perspective of the producers, the actors, relevant information is collected, the effects of the pandemic on the production of national cinema were aggravated by the crisis. On the other hand, the processes of transformation of the modes of production, distribution and marketing were assumed by independent producers. Finally, a trend was found in the national realization focused on the daily life of the confinement and the health crisis that the country was experiencing.